Educide amid conflict: the struggle of the Palestinian education system - Dalal Iriqat; Rula Alousi; Tahani Z. Aldahdouh; Alaa AlDahdouh; Iman Dankar; Dima Alburai; Mohamed Buheji; Abdo Hassoun (Quality Education for All)
Purpose – This paper aims to examine the devastating effects of the ongoing conflict in Gaza on its education system, a phenomenon termed “Educide”. The study documents the systematic destruction of educational infrastructure, including schools and universities, as well as the targeted killing of students and educators, which impedes current and future access to education. The paper argues that this deliberate dismantling of Gaza’s educational institutions aims to erase Palestinian culture, identity and resilience, thus hindering any prospects for SDG4. The authors emphasize the urgent need for international accountability and support to rebuild Gaza’s education sector, preserving its role in societal development, identity preservation and human rights. Design/methodology/approach – This research paper uses a qualitative design, using data gathered through a comprehensive review of both grey and scholarly literature to assess the impact of the ongoing conflict on Gaza’s education system. By analyzing official reports, working papers and conference abstracts, the study compiles evidence of the systematic targeting and destruction of educational infrastructure in Gaza. This approach allows for an in-depth understanding of the conflict’s immediate and long-term effects on educational access, infrastructure and cultural preservation. The methodology underscores the critical implications of these findings and calls for urgent international intervention and accountability to protect education in conflict zones. Findings – The paper’s findings reveal severe, systematic destruction of Gaza’s educational infrastructure, including schools and universities, with extensive loss of life among students and educators. The research shows that this “Educide” disrupts educational access for current and future generations, stifles intellectual growth and threatens the preservation of Palestinian identity and heritage. Evidence indicates that such deliberate targeting aims to destabilize Gaza’s social structure and hinder long-term development. The findings highlight the urgent need for international accountability to halt these acts, safeguard education as a fundamental right and rebuild Gaza’s education system to ensure resilience and continuity amid conflict. Research limitations/implications – The research faces several limitations, including reliance on secondary sources, such as gray literature and official reports, which may limit firsthand insights and real-time data accuracy. In addition, the ongoing nature of the conflict restricts access to updated information and complicates direct assessment of damage. The study’s qualitative approach may also limit the ability to quantify the full extent of destruction and long-term impacts on educational outcomes. Finally, the challenging political environment may affect the availability and reliability of certain sources, potentially leading to gaps in comprehensive data on Gaza’s educational infrastructure and human resource losses. Practical implications – The practical implications of this paper underscore the urgent need for international intervention to protect Gaza’s education sector. Highlighting the concept of “Educide”, the study calls for policies to prevent the targeting of educational institutions in conflict zones and mechanisms to hold perpetrators accountable. It advocates for comprehensive support to rebuild Gaza’s educational infrastructure, ensuring students and educators can safely return to learning environments. This research also serves as a foundation for policymakers, NGOs and human rights organizations to implement sustainable educational recovery programs to preserve Palestinian identity, cultural heritage and long-term development amidst ongoing challenges. Social implications – The social implications of this paper are profound, as it highlights the erosion of Gaza’s educational foundations and its broader effects on Palestinian society. The systematic destruction of schools and universities disrupts education and impacts community resilience, cultural preservation and intergenerational knowledge transfer. This “Educide” undermines social cohesion by depriving young Palestinians of safe learning environments, vital support networks and prospects for socioeconomic stability. The study emphasizes the need for global support to restore these educational spaces, ensuring that education can continue to foster community strength, identity and hope within Gaza’s society amid conflict. Originality/value – This paper is original in its focus on the concept of “Educide” in Gaza, a term describing the systematic targeting and destruction of educational infrastructure as a means of cultural and societal erasure. By framing the deliberate dismantling of Gaza’s education sector within a genocidal context, the paper offers a novel perspective on the intersection of conflict, education and cultural preservation. It contributes uniquely to academic and policy discourse by combining documented evidence with a call for international accountability, emphasizing the critical role of education as both a human right and a foundation for resilient societies in conflict zones.